Perfection of planning innovative of investment activity on the enterprises of Ukraine (Economics and region, 2018)
This article is devoted to the problems of perfection of planning of innovation-investment activity on the enterprises of Ukraine. The basic ways of perfection are considered after the indicated direction with the purpose of activation innovative investment to development of enterprises of Ukraine. The strategic planning of innovation-investment is described investment to the process on an enterprise. The structure of innovative-investment potential of enterprise is analysed. In the article the theoretical and methodological going is systematized near planning the investment providing of innovative development of enterprises. The system of planning of innovations are investigational on enterprises, the ways of development of planning innovative of investment activity are analysed on enterprises.
Keywords: planning innovative of investment activity; innovations; investments; innovative process; innovative investment potential of enterprise; innovative project